Orally administered solasodine, a steroidal glycoalkaloid, suppresses ovalbumin-induced exaggerated Th2-immune response in rat model of bronchial asthma. (1st October 2022) - Arora, Poonam; Nainwal, Lalit Mohan; Gupta, Gaurav; Singh, Sachin Kumar; Chellappan, Dinesh Kumar; Oliver, Brian G.; Dua, Kamal
Abstract: Bronchial asthma is a chronic lung disorder, that affects an estimated 262 million people worldwide, thereby, causing a large socio-economic burden. Drug molecules from natural sources have exhibited a good promise in providing an alternative therapy in many chronic ailments. Solasodine, a glycoalkaloid has received an immense interest due to its large pharmacological and industrial value, however, its usefulness in asthma control has not been investigated till date. In this work, solasodine was tested for its ability to reverse several characteristics of bronchial asthma induced by intraperitoneal injection of ovalbumin (OVA) and aluminium hydroxide in experimental rats. Treating asthmatic animals with solasodine (1 mg/kg b.w. or 10 mg/kg b.w.) or dexamethasone (2.5 mg/kg b.w.) reversed OVA-induced airway hyperresponsiveness, infiltration of inflammatory cells and histamine levels in the airways. Furthermore, as compared to OVA-control rats, allergen-induced elevated levels of IgE, nitrites, nitric oxide, and pro-inflammatory mediators, including TNF-α, IL-1β, LTD-4, and Th2-cytokines, particularly, IL-4, IL-5 were remarkably reduced in both bronchoalveolar lavage fluid and blood. These findings are supported by significant protection offered by various treatments against OVA-induced airway inflammation and mast cell degranulation in mesenteric tissues. Further, In-silico molecular docking studies performed to determine inhibitory potential of solasodine at IL-4 and IL-5, demonstrated strong affinity of phytocompound for these receptors than observed with antagonists previously reported. Results of current study imply that solasodine has therapeutic promise in allergic asthma, presumably due to its ability to prevent mast cell degranulation and consequent generation of histamine and Th2-associated cytokines in airways. Highlights: Solasodine was tested against OVA-induced rat model of bronchial asthma. Solasodine oral treatment reversed airway hyperresponsiveness in asthmatic animals. Solasodine oral treatment inhibited mast cell degranulation in asthmatic animals. Th2 cytokines were reduced after treating asthmatic animals orally with solasodine. Solasodine exhibited affinity for IL-4 and IL-5 receptors.